MENINGKATKAN KEPUASAN KERJA PADA KARYAWAN MATAHARI GROSIR AE GROUP TARUMAJAYA BERDASARKAN ANALISIS PENGARUH KEADILAN ORGANISASI DAN BEBAN KERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Muhammad Julda Al Hafiz; Indah Rizki Maulia; Fahmi Sahlan; Jumawan; Adi Wibowo Noor Fikri (Draf Solusi Indonesia, 2025)
Improving Job Satisfaction of Matahari Grosir AE Group Tarumajaya Employees Based on the Analysis of the Influence of Organizational Justice and Workload with Work Motivation as an Intervening Variable.This research analyzes the influence of organizational justice and workload on employee job satisfaction and work motivation at Matahari Grosir AE Group Tarumajaya, with work motivation as an intervening variable. The research aims to examine both the direct and indirect effects of these variables. Using the saturation sampling method, the entire population of 56 employees was selected as the sample. Primary data was collected through observations, interviews, and questionnaires, then analyzed using the Partial Least Square (PLS) method with SMARTPLS 4.1. The findings indicate that organizational justice and workload have a positive and significant impact on job satisfaction and work motivation, both directly and through motivation as a mediating variable. This research is beneficial for companies in designing policies to enhance employee satisfaction and motivation. For employees, it provides insights into the importance of factors affecting job satisfaction and motivation. Additionally, for researchers, the results contribute to a deeper understanding of the relationships between organizational justice, workload, job satisfaction, and work motivation.